The EFFECTS OF CAJUPUT AND CITRONELLA GRASS AS HOST PLANTS ON SANDALWOOD GROWTH : Sandalwood plant growth - Joni Tefnai; Irdika Mansur; Nurheni Wijayanto (Department of Forest Resources Conservation and Ecotourism - IPB University, 2021)
Sandalwood (S. album) is native species in eastern Indonesia, especially East Nusa Tenggara (NTT). Its species can produce essential oils and have been known to foreign countries. However, the community's interest in planting sandalwood is low due to a lack of knowledge regarding cultivation techniques and a long harvest period. The purpose of this study was to assess the growth of sandalwood (S. album) with cajuput (M. cajuputi) citronella grass (C. nardus) as the host plant. The research was conducted in Fatunisuan Village, Miomaffo Barat Subdistrict, TTU Regency using a completely randomized design (RAL) of 4 treatments and 3 replications, namely sandalwood without a host (K), sandalwood with cajuput host (CKP), sandalwood with citronella grass as the host plant (CSW), and sandalwood with cajuput and citronella grass as host plants (CKPSW). Data analysis used variance at 95% confidence level. Analysis of variance, which showed that the treatment had a significant effect, was further tested using the Duncan Multiple Range Test (DMRT) at the 5% level. The results showed that the mixed system using two types of hosts, namely lemon grass, cajuput or both, significantly increased the growth of sandalwood in the field. The CKPSW treatment gave the highest percentage increase in sandalwood growth compared to other treatments. Key words: cajuput host, citronella grass host, RAL, sandalwood